Comparative Evaluation of Retention of Different Luting Cements for Im plant-Supported Crowns: An In Vitro Study (Academia Journal of Medicine, 2026)
Background: Retention of implant-supported crowns is a critical factor influencing the long-term success of implant prostheses. The choice of luting cement plays an important role in determining the retentive strength, retrievability, and clinical performance of cement retained implant restorations. Aim: To comparatively evaluate the retention of implant-supported crowns cemented with zinc phosphate cement, resin cement, and resin-modified glass ionomer cement using a universal testing machine in an in vitro setting. Materials and Methods: Thirty implant–abutment–crown assemblies were fabricated and divided into three groups (n = 10) based on the luting cement used: Group I—zinc phosphate cement, Group II—resin cement, and Group III—resin-modified glass ionomer cement. Standardized full-coverage metal crowns were cemented onto prefabricated titanium abutments following manufacturer instructions. All specimens were stored in distilled water at 37°C for 24 hours. Retention was evaluated by applying a tensile load along the long axis of the implant using a universal testing machine at a crosshead speed of 1 mm/min until crown dislodgement occurred. The maximum pull-out force required was recorded in Newtons and statistically analyzed. Results: The highest mean retentive strength was observed in the resin cement group, followed by resin-modified glass ionomer cement, while zinc phosphate cement demonstrated the lowest retention. Statistical analysis revealed a significant difference in pull-out force values among the three groups (p < 0.05). Conclusion: Within the limitations of this in vitro study, resin cement provided superior retention for implant-supported crowns compared to resin-modified glass ionomer cement and zinc phosphate cement. Selection of luting cement should consider the balance between retention requirements and the need for retrievability in implant prosthodontics.
Keywords: Implant supported crowns; Luting cements; Retention; Pull-out force; In vitro study